The Compassionate Engagement and Action Scales for Self and Others: Turkish Adaptation, Validity, and Reliability Study - Ari, Ela; Cesur-Soysal, Gizem; Basran, Jaskaran; Gilbert, Paul (Frontiers in Psychology, 2022)
Aim This study aims to translate the Compassionate Engagement and Action Scales (CEAS) into Turkish and to test their subsequent validity, reliability, and psychometric properties. Turkey is one of the blended cultures with eastern and western elements under the influence of traditional religion. This cultural diversity brings about a rich context to study compassion and its relationship to mental health. The scales assess the ability to be sensitive to suffering and engage and then take helpful actions in compassion. The motivation for compassionate engagement and action is measured at three ‘flows’ as follows: (1) compassion for others; (2) compassion from others; and (3) compassion for self. Methods The sample consists of 525 college students aged 18 years or older. The participants completed the CEAS Turkish Form for Others, Self and from Others, Self-Compassion Scale Short Form, Compassionate Love Scale, and Self-Criticism Scale. Results The confirmatory factor analyses were conducted using AMOS version 27 to examine the validity of the three scales with two different factor structures each. All the three models show good fits to the data. The Cronbach’s alpha coefficient for the CEAS for Others and for Self and from Others are good to excellent (between 0.70 and 0.95 for all subscales). Compassion for self, compassion for others, and compassion from others correlated modestly. Conclusion It can be concluded that the Turkish version of the Compassionate Engagement and Action Scales for Others and Self and from Others has sufficient psychometric properties and can be used as a reliable and valid measure to assess compassionate engagement and action.